The current landscape of cancer treatment scenario in Bangladesh - Karmakar, Priyam; Roy, Abhijeet (International Journal Of Community Medicine And Public Health, 2024)
The current cancer scenario in Bangladesh presents a significant public health challenge. Cancer is the second leading cause of death in the country, with approximately 150,000 new cases diagnosed and 108,000 deaths annually. Bangladesh is facing several critical issues regarding cancer treatment like the lack of a national cancer control strategy and comprehensive cancer screening system, resulting in most patients being diagnosed at advanced stages, which reduces the chances of successful treatment. Early detection and prevention measures are crucial, but efforts in these areas remain inadequate in Bangladesh.